Graduate study in criminology and criminal justice : a program guide - Prior, Nicole M. (Nicole Mary) (Routledge, 2015)
This book provides information on graduate programs in the United States and Canada to students and professionals who are interested in attending post-baccalaureate education in criminology or criminal justice. The book contains information for each program and includes both brick-and-mortar and online programs. An introduction and a section on potential employment options provide context.